Biopsy proven cerebral toxoplasmosis presenting as an initial manifestation of HIV infection - Chopra, Puneet; Kaur, Asees; Sraw, Sushma; Singhal, Vinay; Nirmal, Jasmine (International Journal of Research in Medical Sciences, 2025)
We present an unusual case of a 45 years male patient presenting with subacute onset of headache, persistent nausea and seizure episodes. He was initially started on anti-tubercular (ATT) drugs empirically at outside hospital based on Magnetic resonance imaging (MRI) findings of brain stem lesions. Patient presented at our institute with progressive worsening of neurological symptoms and radiological findings. He did not have risk factors for immunosuppression or human immunodeficiency virus (HIV) infection. Stereotactic biopsy from the occipital lesion was performed in view of diagnostic uncertainty and worsening clinical condition which revealed the diagnosis of cerebral toxoplasmosis. Patient subsequently tested positive for HIV via fourth generation combination immunoassay. Our case highlights the observation that cerebral toxoplasmosis can rarely present as an initial manifestation of HIV infection and stereotactic brain biopsy, if feasible, can guide in making a clinical decision in patients who have diagnostic uncertainty regarding focal brain lesions.